(untitled) (Revista Electrónica REDINE, 2018)
The present work is the development of digital maps from remote images in order to understand the landscape of Yacambú National Park, to enrich the geography and update information in the region under study. Methodologically aerial photographs, satellite images SPOT-5, Landsat-5 and sectional sheets were used. The information developed in the "ArcView-GIS 3.2" program, allowing to build a geographical basis characterization and digital mapping in detail, analyzing and interpreting each present in the landscape ecological unit. The applicability is based on the regional approach, which generates knowledge and skills for geographic analysis, since hand with new technologies emerging integrated citizens with eco-social consciousness in the man- nature-economy relations. It is useful to note that the results showed that the region under study is of great value economic, ecological, agricultural, geographical and tourism, due to its extensive water network.